Serum antioxidants and inflammation predict red cell distribution width in older women: The Women's Health and Aging Study I - Semba, Richard D.; Patel, Kushang V.; Ferrucci, Luigi; Sun, Kai; Roy, Cindy N.; Guralnik, Jack M.; Fried, Linda P. (Clinical nutrition (Edinburgh, Scotland), 2010)
Red cell distribution width (RDW), a measure of heterogeneity in the size of circulating erythrocytes, is associated with some chronic diseases and predicts mortality. Although oxidative damage and inflammation have been theorized to affect RDW, the relationships of antioxidants and inflammation with RDW have not been well characterized. The aims were to determine whether total serum carotenoids, α-tocopherol, selenium, protein carbonyls, and interleukin-6 (IL-6) are associated with RDW and predict RDW over time. RDW was measured at baseline, 12 months, and 24 months follow-up in 786 moderately to severely disabled community-dwelling women, aged ≥65 years, in the Women's Health and Aging Study I in Baltimore, Maryland. Selenium was significantly associated with RDW at baseline and predicted RDW over two years' follow-up in separate multivariate mixed-effects models that adjusted for other covariates. As expected, the addition of IL-6 to the models attenuated the association of serum selenium with RDW, as low antioxidant levels are known to upregulate IL-6. Total carotenoids were associated with RDW at baseline and one year follow-up. Protein carbonyls and α-tocopherol were not significantly associated with RDW. Serum selenium is an independent predictor of RDW and may potentially mediate effects on RDW through IL-6.